2002
DOI: 10.1046/j.1461-0248.2002.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of tool‐use in the woodpecker finch (Cactospiza pallida)

Abstract: Insects, mammals and birds are known to use tools, but empirical evidence of the ecological importance of tool-use is scarce. Here, we present the first ecological study of tool-use by a bird species. Woodpecker finches use twigs or cactus spines to pry arthropods out of tree-holes. We compared tool-use during wet and dry seasons in two different vegetation zones: the Arid Zone and the humid Scalesia Zone. In the Scalesia Zone, where food was abundant and easily accessible, woodpecker finches rarely used tools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
85
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 26 publications
1
85
1
Order By: Relevance
“…In other words, it remains an open question whether ancestors of NC crows possessed morphological features that predisposed them to tool manufacture and use, or whether tool-use behaviour was expressed first due to unusual ecological opportunities, before exerting selection pressures that gradually shaped the species' visual system and bill morphology 6 . Evidence that unusual ecological conditions have been major drivers in the evolution of habitual tool use is provided by detailed analysis of the foraging ecology of wild NC crows 6,18,19 and woodpecker finches Cactospiza pallida 20 , and the experimental results for rooks (see above). These avian study systems promise valuable, phylogenetically independent comparisons with the hominin lineage, where the evolution of opposable thumbs and flexible wrists in humans has enabled precision pinching and unprecedented tool-handling capabilities [2][3][4]15,16,21 .…”
Section: Discussionmentioning
confidence: 99%
“…In other words, it remains an open question whether ancestors of NC crows possessed morphological features that predisposed them to tool manufacture and use, or whether tool-use behaviour was expressed first due to unusual ecological opportunities, before exerting selection pressures that gradually shaped the species' visual system and bill morphology 6 . Evidence that unusual ecological conditions have been major drivers in the evolution of habitual tool use is provided by detailed analysis of the foraging ecology of wild NC crows 6,18,19 and woodpecker finches Cactospiza pallida 20 , and the experimental results for rooks (see above). These avian study systems promise valuable, phylogenetically independent comparisons with the hominin lineage, where the evolution of opposable thumbs and flexible wrists in humans has enabled precision pinching and unprecedented tool-handling capabilities [2][3][4]15,16,21 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be clear from the foregoing that components of models that rely, even in part, on innate factors such as intelligence and manual dexterity [62] are insufficient to explain the differences between wild and captive tool-use behaviour. Extrinsic factors, whether social [65], behavioural [2] or ecological [66,67], are therefore essential to a complete explanation of how and why tool use develops. Although in a speculative form, the implications and relevance of the captivity bias effect could likely complement existing studies of technological development in each hominin species (and population within each species).…”
Section: (B) Factors Promoting Captivity Biasmentioning
confidence: 99%
“…have also come to the forefront as prominent tool users. Woodpecker finches in the Galápagos Islands use twigs or cactus spines to pry arthropods from tree holes [20]. Tebbich et al [21] recently reported woodpecker finches using tools manufactured from barbed twigs of introduced blackberry bushes to extract prey from under the bark of a native tree species, demonstrating their abilities to modify tools in a flexible manner and exploit novel environmental opportunities.…”
Section: Introductionmentioning
confidence: 99%